Does the Tenure of Private Equity Investment Improve the Performance of European Firms? - Oleg Badunenko; Christopher F. Baum; Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The paper investigates whether the presence and tenure of Private Equity (PE) investment in European companies improves their performance. Previous studies documented the unambiguous merit of a buyout during the 1980s and 1990s for listed firms in the US and UK markets. This study analyzes such influences in both listed and unlisted European firms during 2002-2007. Our analysis suggests that short-term PE investments have, on average, a detrimental effect on firm performance. The performance of a firm that has PE backing is lower than that of a firm without PE backing in the first year of PE investment. Such an effect disappears if PE investments remain in the firm for an uninterrupted six-year term.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: M14; G24; G34; 330; Private equity financing; corporate finance